2018
DOI: 10.1177/1055665618767425
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Cortisol Rhythms in Children With Cleft Lip and/or Palate

Abstract: Five- and 10-year-old children with corrected CL/P seemed not to be more stressed than controls, and there were no correlation to HRQoL. The HRQoL levels - were comparable to that of a European norm population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 38 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…In addition, one of the children had the highest level of salivary cortisol (0.199 µg/dL), which may have interfered with the median cortisol in this group as a whole. In a study 33 that associated the stress response through cortisol and a health-related quality of life questionnaire (KIDSCREEN-52), performed with the participation children with CLP aged 5 to 10 years and a control group paired by age, the authors found that there was no difference in cortisol concentrations between children with different types of cleft. The study concluded that children with CLP did not show a higher level of stress compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, one of the children had the highest level of salivary cortisol (0.199 µg/dL), which may have interfered with the median cortisol in this group as a whole. In a study 33 that associated the stress response through cortisol and a health-related quality of life questionnaire (KIDSCREEN-52), performed with the participation children with CLP aged 5 to 10 years and a control group paired by age, the authors found that there was no difference in cortisol concentrations between children with different types of cleft. The study concluded that children with CLP did not show a higher level of stress compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of a correlation between the level of cortisol and the quality of life of children with CLP has also been demonstrated in a previous research. 33 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation